Innovative and green nanolime treatment tailored to consolidate the original mortar of the façade of a medieval building in L'aquila (Italy). (10th October 2019) - Taglieri, G.; Daniele, V.; Macera, L.; Mignemi, A.
Highlights: Green and compatible conservative treatments on historic mortars. The treatments are performed by a new aqueous nanolime suspension. The whitening threshold is determined in relation to the suspension concentration. Surface cohesion test and drilling resistance measurements are performed. In situ application of our new nanolime and evaluation of treatment effectiveness. Abstract: This paper presents an original, green and compatible treatment to consolidate the pointing lime plastering of the façade of a medieval Italian palace, subjected to detachments and pulverization phenomena. The cohesion between the mortar constituents was refurbished by an aqueous nanolime suspension, synthesized by a cheap, time/energy-saving and scalable method, here originally tested on historic mortars. The suspension showed a high reactivity, assuring a complete carbonation in few hours, "restoring" the binder fraction with a new-formed network of calcite nanoparticles. The treatment efficacy was evaluated by chemico-physical, mineralogical and mechanical characterization both on untreated and treated specimens.